2008
DOI: 10.1038/sj.npp.1301656
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and Subcortical 5-HT2A Receptor Binding in Neuroleptic-Naive First-Episode Schizophrenic Patients

Abstract: The serotonin 5-HT 2A receptor is suspected to be involved in a number of psychiatric disorders, including schizophrenia. In particular, atypical antipsychotics have antagonistic effects on the 5-HT 2A receptors, supporting a specific role of the 5-HT 2A receptor in the pathophysiology of this disease. The aim of this study is to investigate cortical and subcortical 5-HT 2A binding in neuroleptic-naive schizophrenic patients. Fifteen neuroleptic-naive patients diagnosed with schizophrenia (age 27.5 ± 4.5 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 45 publications
1
47
1
Order By: Relevance
“…However, both tracers suffer from a relatively low affinity for 5-HT 2A receptors and, thus, they have an insufficient signal-to-noise ratio in subcortical areas (Erritzoe et al, 2008). In contrast, one study using (Erritzoe et al, 2008).…”
Section: Included Cases Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…However, both tracers suffer from a relatively low affinity for 5-HT 2A receptors and, thus, they have an insufficient signal-to-noise ratio in subcortical areas (Erritzoe et al, 2008). In contrast, one study using (Erritzoe et al, 2008).…”
Section: Included Cases Ofmentioning
confidence: 99%
“…However, both tracers suffer from a relatively low affinity for 5-HT 2A receptors and, thus, they have an insufficient signal-to-noise ratio in subcortical areas (Erritzoe et al, 2008). In contrast, one study using (Erritzoe et al, 2008). Two further studies investigated 5-HT 2A receptor density with [ 18 F]altanserin PET in subjects supposed to be in a prodromal state of schizophrenia and reported both decreased binding of the radio tracer in the PFC (Hurlemann et al, 2005(Hurlemann et al, , 2008.…”
Section: Included Cases Ofmentioning
confidence: 99%
“…[31][32][33][34][35] The majority of these studies, including our own, 54 were unable to identify differences in cortical serotonin 2A binding between schizophrenic patients and healthy control subjects. In our previous study 38 we found increased serotonin 2A receptor binding in the caudate nucleus.…”
Section: Commentmentioning
confidence: 99%
“…Fifteen of the patients were identical to the patients included in our previous preliminary study. 35 A decrease in serotonin 2A binding in the frontal cortex in these patients compared with matched healthy control subjects was expected a priori. We also expected to confirm our preliminary finding of serotonin 2A receptor upregulation in the caudate nucleus.…”
mentioning
confidence: 99%
See 1 more Smart Citation